Pengaruh Kepemimpinan Transformasional, Motivasi Kerja Dan Iklim Kerja Terhadap Kinerja Karyawan Medis: Survey Pada Rumah Sakit Umum Daerah di Kota Tarakan-Kalimantan Utara - Andri Yogi Adyatma Prasetyo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Hospital as a public health care organization , function to serve the wider community in the form of services. To achieve the desired objectives of management , the hospital requires employees to improve performance. Hospital employees require a leader who has a leadership style , working climate and motivate a careful manner , in order to achieve all the targets in the desired so that human resources can reflect the culture in an organization. In this study using survey method with 162 medical staff in hospitals of Tarakan City as research respondents. Obtained partial results of transformational leadership has positive influence on employee performance , as well as the motivation effect has a positive influence on employee performance and also the working climate positive influence on employee performance. While simultaneously, variable transformational leadership, motivation and work climate has positive influence on employee performance medical in Tarakan Hospital . From the results of this study suggest that for an organization to maintain the quality of leadership, motivation and work climate so that the employee's performance will remains good.